Miejsce zwykłego pobytu dziecka — uwagi na tle wyroków Trybunału Sprawiedliwości Unii Europejskiej z dnia 28 czerwca 2018 r. (C-512/17) oraz z dnia 17 października 2018 r. (C-393/18 PPU) - Bobrzyńska, Olga (Problemy Prawa Prywatnego Międzynarodowego, 2020)
In cases C-512/17 and C-393/18 PPU, the national courts raised doubts as to the significance of the circumstances that should be taken into account in determining the habitual residence of a child. In particular the issue was whether the child’s physical presence is a prerequisite in order to recognize that a child has his habitual residence in the country concerned. In its judgment of 17 October 2018, the Court of Justice found that a child must be physically present in a Member State in order to be regarded as habitually resident in that Member State. The parent’s intention cannot be assigned a decisive role. The arguments in this respect are consistent with the interpretation of the concept of habitual residence laid out in the earlier judgment of 28 June 2018, in which the Court of Justice connected the habitual residence of the child with the place where the centre of that child’s life is actually situated, and not with the place where the child would have lived in accordance with the plans of one of the parents. The Court’s interpretation can be attributed to the so-called combined model of determining a habitual residence by looking for child’s centre of interest, taking into account a number of circumstances, including the intention of parents with parental responsibility. Physical presence has rightly been recognized as a necessary condition for establishing jurisdiction under Regulation No 2201/2003 based on habitual residence.